COVID‐19 Alpha Variant (B.1.1.7): Humoral, memory B and T cells in COVID‐19 pediatric convalescents. Issue 10 (6th October 2022) - Gurevich, Michael; Zilkha‐Falb, Rina; Sonis, Polina; Magalashvili, David; Dolev, Mark; Mandel, Mathilda; Menascu, Shay; Achiron, Anat
Abstract: Background: Studies of anti‐SARS‐CoV‐2 humoral and adaptive response in COVID‐19 non‐vaccinated pediatric convalescents are controversial and further evidence from the pediatric population are needed. Objectives: To elucidate SARS‐CoV‐2 humoral and memory B‐ and T‐cells responses in pediatric convalescents as compared with the adult. Methods: Blood samples were obtained from 80 non‐vaccinated, IgG‐positive, COVID‐19 convalescents (age 8.0–61.0 years), 4.0 months from onset. Frequency of responders and magnitudes of SARS‐COV‐2 IgG, memory B‐cells (MBC) and IFNg‐ and IL2‐secreting memory T‐cells (MTC) in response to immuno‐dominant peptide pools in pediatric, young adults and middle‐aged adults with onset age 8–18 years ( N = 20), 19–39 years ( N = 30) and 40–61 years ( N = 30), respectively, were analyzed. SARS‐CoV‐2 IgG were detected by ELISA (Euroimmun, Germany). MBC, IFNg‐, IL2‐ and IFNg+IL2‐secreting MTC (IFNg‐MTC, IL2‐MTC and IFNg+IL2‐MTC) were detected using FluoroSpot (Mabtech, Sweden). Results: MBC level was lower in pediatric as compared with the middle‐aged adults (median 12.75 interquartile range [IQR] 4.27–33.7 and 32.0 IQR 6.0–124.2, respectively, p = .003). MBC level in young adults was lower than in middle‐aged adults (median 18.5 IQR 1.7–43.8 and 32.0 IQR 6.0–124.2, respectively, p = .006). The level of IL2‐MTC was lower in the pediatric group as compared with middle aged‐adults (median 2.1 IQR 0–16.9 and 28.6 IQR 11–49.6, respectively, p < .03) and in young adults lower than in middle‐aged adults (median 1.45 IQR 0–18.6 and 28.6 IQR 11–49.6, respectively, p = .02). In addition, the level of IFNg‐MTC was lower in pediatric as compared with young adults (median 4.25 IQR 0.0–15.0 and 20.9 IQR 0–75.2, respectively, p = .05). The level of IgG was comparable between pediatric and both young and middle‐aged adult groups (4.82 ± 2.95, 3.70 ± 2.65 and 4.9 ± 2.94, respectively, p > .34). Conclusion: Non‐vaccinated COVID‐19 pediatric convalescents have lower adaptive immune responses than adults sustaining the recommendation for vaccination of the pediatric population.